2019
DOI: 10.1186/s12935-019-1038-0
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stromal cells induce inhibitory effects on hepatocellular carcinoma through various signaling pathways

Abstract: Hepatocellular carcinoma (HCC) is the most prevalent type of malignant liver disease worldwide. Molecular changes in HCC collectively contribute to Wnt/β-catenin, as a tumor proliferative signaling pathway, toll-like receptors (TLRs), nuclear factor-kappa B (NF-κB), as well as the c-Jun NH2-terminal kinase (JNK), predominant signaling pathways linked to the release of tumor-promoting cytokines. It should also be noted that the Hippo signaling pathway plays an important role in organ size control, particularly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 143 publications
0
13
0
Order By: Relevance
“…Mesenchymal stromal cells (MSCs) are the cells with the unique ability to exert suppressive and regulatory effects on the immune system [15]. MSCs have been the focus of research because evidence has indicated that MSCs are able to migrate to and return from damaged tissues, exercise potent anti-inflammatory and immune regulatory activities, support the regeneration and repair of tissues, resist against apoptosis, inhibit tissue fibrosis, and decrease tissue injury [16].…”
Section: Mesenchymal Stromal Cells and Their Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Mesenchymal stromal cells (MSCs) are the cells with the unique ability to exert suppressive and regulatory effects on the immune system [15]. MSCs have been the focus of research because evidence has indicated that MSCs are able to migrate to and return from damaged tissues, exercise potent anti-inflammatory and immune regulatory activities, support the regeneration and repair of tissues, resist against apoptosis, inhibit tissue fibrosis, and decrease tissue injury [16].…”
Section: Mesenchymal Stromal Cells and Their Featuresmentioning
confidence: 99%
“…On the other hand, inflammation leads to nuclear factor-kappa B (NF-κB) and c-Jun NH2-terminal kinase (JNK) signaling, which is also controlled through the factors secreted by MSCs. In addition, lung damage improves during the response of MSCs to oxidative stress, cytoprotection, and phosphoinositide 3-kinase/protein kinase B (P13K / Akt) signaling pathway [25]. Administration of BM-MSCs alleviated lung injury in a preclinical study via potentiating the PI3K/Akt signaling pathway [26,27].…”
Section: Mesenchymal Stromal Cells and Their Featuresmentioning
confidence: 99%
“…Clearly, the tumor cells and their microenvironment may have an influence on the action of recruited MSCs [59]. Taken together, both postulations seem concomitantly true and therefore, it is very hard to make a prediction to the effects of MSCs on the cancerous process [60,61]. tumor-promoting or a tumor-limiting effects depending on the experimental circumstances [13].…”
Section: Dual Roles Of Mscs In Liver Cancermentioning
confidence: 99%
“…To author knowledge, MSCs have shown tumor suppressive effects in induced murine HCC that were linked to down regulation of Wnt signaling target genes [60,62]. There are several suggested mechanisms lying behind this action.…”
Section: Mechanisms Of Msc-dependent Tumor Suppression In Liver Cancermentioning
confidence: 99%
“…Despite encouraging progress was acquired, treatments for patients with advanced HCC are still very limited owing to acquired sorafenib resistance, and further development of new treatment options is necessary. In addition, the low response rate of sorafenib is a worrying phenomenon and epithelial-mesenchymal transition (EMT), Ras/Raf/MAPK, PI3K/Akt, JAK/STAT pathways, hypoxia, and many other mechanisms were considered to be the main obstacles that led to the failure of sorafenib in HCC patients [9][10][11].…”
Section: Introductionmentioning
confidence: 99%